PENGARUH TINGKAT SENTRALISASI, PENGENDALIAN DAN SISTEM AKUNTANSI MANAJEMEN TERHADAP EFEKTIVITAS KINERJA PENGURUS UNIT PENGELOLA KEGIATAN (Studi Kasus Pada Program Nasional Pemberdayaan Masyarakat Mandiri Perdesaan di Kabupaten Boyolali) - KUSUMA , IMAM WILIA (2011)
Executive Management Unit (UPK) is expected to remain there and become the informal micro-credit institutions that can continue to be accessed (used) by the poor (especially women). UPK current condition and its development will determine the sustainability of UPK as one of the informal micro-credit institutions in Indonesia. This is needed for UPK to reach the poor in greater numbers again. The existence and activities of UPK institutions currently have analyzed whether the future can be developed microfinance institutions and sustainable so that it can continue to serve the credit especially for the poor who need it. To improve the effectiveness of institutions such UPK in managing micro-credit, must be addressed before of the degree of centralization, control, and management accounting systems, so that as the institutions that manage micro-credit activities UPK has a strong management fundamentals and accountable. The purpose of this study was to analyze the influence of centralization, control and management accounting systems on the effectiveness of the performance of Executive Management Unit Activity in the district of Boyolali. The population of this research is the managers who work in office UPK located in Boyolali district, amounting to 16 offices UPK. The sample in this research is UPK managers who work in offices located in the district UPK Boyolali with a minimum age 1 year institution, have financial statement data and complete administration, amounting to 16 Districts. Based on the results obtained by distributing questionnaires sample size 48 respondents. Methods of data collection using questionnaires and methods of data analysis using multiple regression analysis. Based on the results of data analysis can be summarized as follows: centralization but not significant positive effect on the effectiveness of performance. Means the higher centralization will further improve the effectiveness of performance. This control has positive and significant impact on performance effectiveness. Means the better control will further improve the effectiveness of performance. Management accounting system has positive and significant impact on performance effectiveness. Means the better the management accounting system will further enhance the effectiveness of performance. centralization, control, management accounting system jointly significant effect on performance effectiveness. This control dominant influence